FIQH IQTISHAD SEBAGAI SUMBER PENGEMBANGAN EKONOMI DAN KEUANGAN ISLAM - Rahmawati, Indriyani Dwi; Mustofa, Mustofa (Universitas Nurul Jadid, 2024)
The economic scope is increasingly complex, guidelines are needed to solve all problems that arise based on Islamic sharia principles. Fiqh iqtishad has a very important role to be a reference for the community in Islamic economics and finance. Therefore, the study of this article aims to find out how fiqh iqtishad is a source of Islamic economic and financial development. This study uses a narrative qualitative approach with a literature review method with data presented from books, scientific journals, al-Quran, hadith, MUI facts, related to fiqh iqtishad, economic and financial development. The results of the study show that fiqh iqtishad develops dynamically and follows economic and financial developments. In Indonesia itself, a DSN-MUI fatwa emerged as one of the products of ijtihad. Fatwa is the result of the reasoning of Islamic jurists in providing answers and responses to contemporary problems that are optional and non-binding, only as an explanation of the problems raised by the fatwa requester